Exigência de lisina de juvenis de Surubim (Pseudoplatystoma spp) - Samuel de Assis Prado (2011)
The determination of nutritional requirements, especially the amino acids requirements, is capital to the economical success of modern aquaculture. The aim of this study was determinate the lysine requirement of surubim (Pseudoplatystoma spp) juvenile. Six hundredsurubim juvenile weighting 38,2 ± 1,53 was randomly placed in twenty 400 litters tanks. The experimental design was entirely randomized with five lysine levels and four replicates. Each tank containing 30 fish was considered an experimental unit. Data was submitted to ANOVAto verify the significance of the regression models suggested using the statistical software SAEG (Universidade Federal de Viçosa). In the attempt to determinate the lysine requirement, results of weight gain, average weight gain, feed consumption, feed conversion, protein efficiency rate, beyond the levels of crude protein, fat, crude energy and ash on the carcass, where used to obtain regression equations. Except for the average weight gain all the analyzed parameters where significant for the linear effect, indicating the higher level as the one that gives the best results. Tested parameters where significantly affected by increasing dietary lysine levels. The best results where promoted by the higher lysine diet.